Primary breast sarcoma in a middle age lady: a rare presentation - Mashudan, Adzwani; Tang, X. J.; Wan Salleh, Wan Muhamad Salahudin; Harun, Norra; K. A., Aina (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Sarcoma is an aggressive, malignant condition of a breast. It is a rare condition, which makes it difficult to diagnose at clinicopathological study. We are reporting a case of a primary breast sarcoma in a 54-year-old menopausal lady that came with painless fast growing right breast lump within 6 months of duration. Clinically, there was a huge mobile painless right breast lump without discoloration of skin noted. Both axilla and supraclavicular lymph node were not palpable. A mammogram showed large lobulated dense mass 8.3cm x 10.0cm in size occupying right upper outer quadrant correspond to BIRADS 4 lesion. A trucut biopsy reported as a papillary lesion. Repeated trucut biopsy reported as mesenchymal lesion with smooth muscle differentiation. With this histopathology report, she was diagnosed with mesenchymal tumor of right breast. She underwent an uneventful mastectomy. Histopathological examination of the surgical specimen reported as tumor with mesenchymal differentiation which requiring further confirmation by breast-endocrine pathologist as primary breast sarcoma. She was subjected to post op radiotherapy to the chest wall followed by adjuvant chemotherapy. © 2018 International Islamic University Malaysia.